Analisis Kelayakan Usaha Pemanfaatan Bungkil Jagung dalam Pengomposan Pelepah Kelapa Sawit - Saragih, Dina Arfianti; Yosephine, Ingrid Ovie; Guntoro, Guntoro; Pradana, Fery (UNIVERSITAS LABUHANBATU, 2022)
Palm oil midrib can also be used as a base for composting. Palm fronds which have been underutilized by the community and are more wasteful are usually only stacked around the tree. One way to use oil palm leaf fronds as a source of plant nutrients is in the form of compost. Palm oil fronds contain high lignin, so the process of composting oil palm fronds takes a long time. The process of decomposition of oil palm fronds naturally takes a long time which is around 3-4 months. This study will analyze the feasibility of utilizing corn meal as a compost material for oil palm fronds, corn meal is used as an energy source for microorganisms to accelerate the decomposition of oil palm fronds.This research was conducted in the greenhouse of the Agricultural Agribusiness College of Agriculture (STIPAP) Medan. When the research was conducted for 3 months, from March to May 2019. Palm oil fronds composting is 50 kilograms with a production cost of Rp 1,121,308 and a total income of Rp 1,200,000. The net profit of making oil palm frond compost is Rp. 78,692. BEB the price of making palm oil compost is Rp. 22,426 while the selling price of compost is Rp. 24,000. The BEP of producing oil palm fronds compost obtained is 47 kilograms while the amount of production of oil palm frond compost making is 50 kilograms so it can be interpreted that BEP production of oil palm frond composting is profitable because the amount of production of BEP production is greater. R / C ratio, which is the ratio of total receipts with total production costs has an R / C value of 1.07, then the R / C value can be greater than 1, it can be interpreted that the R / C value of making compost makes a profit. B / C ratio, which is the ratio of profits to total production costs has a B / C value of 0.07, thus the B / C value is smaller than 1. Then it can be interpreted that the B / C value of making compost does not benefit or is not feasible to run in the production of 50 kilograms.Â Keywords: palm fronds, compost, corn meal, break event point